Optimization of Illuminance and Color-Temperature Conditions for Railway Passengers’ Comfort Based on Oxygenated Hemoglobin Saturation in the Brain - Minkyeong Kim; Jooyeon Lee; Yonghee Lee; Duckshin Park (Toxics)
Railway travel is an eco-friendly means of transportation, and passengers are spending increasing amounts of time on trains while engaging in various activities. As a major factor affecting railway passengers’ comfort, we investigated the effects of lighting. Korean train cars are required to have two rows of light-emitting diode lights with a minimum illuminance of 500 lx, so we examined changes in cerebral blood flow under various illuminance conditions around this threshold value. We used functional near-infrared spectroscopy to measure prefrontal cortex activation in 29 college students under illuminance values of 300, 500, and 800 lx and color-temperature values of 2700 K (bulb color), 4000 K (white color), and 5500 K (blue color). Mean brain activity values were compared using analysis of variance. Of the 48 channels, significant interaction effects between color and illuminance on brain activation responses were observed for channel 38, as well as in the right dorsolateral prefrontal cortex among the different brain regions of the Brodmann area (p < 0.05). Oxygenated hemoglobin concentrations had consistently negative values for all the treatment combinations, and individual treatment analyses based on single-sample Student’s t-tests showed different degrees of brain activation among channels and Brodmann areas. Meanwhile, a comparison of absolute values indicated that an illuminance level of 500 lx was more comfortable than levels of 300 and 800 lx, and that white color was more comfortable than bulb color and blue color. These results provide a scientific basis for the design of train cars that improve passenger comfort and satisfaction, which is anticipated to enhance the quality of railway services.